2008
DOI: 10.1242/dev.013763
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of PDGFRα-initiated PI3K activation and migration of somite derivatives leads to spina bifida

Abstract: Spina bifida, or failure of the vertebrae to close at the midline, is a common congenital malformation in humans that is often synonymous with neural tube defects (NTDs). However, it is likely that other etiologies exist. Genetic disruption of platelet-derived growth factor receptor (PDGFR) ␣ results in spina bifida, but the underlying mechanism has not been identified. To elucidate the cause of this birth defect in PDGFR␣ mutant embryos, we examined the developmental processes involved in vertebrae formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 84 publications
3
41
0
Order By: Relevance
“…PDGFRα signals through PI3 kinase to AKT activation Experiments in mice have suggested that one of the major signalling pathways downstream of PDGFRα is activation of PI3 kinase (Klinghoffer et al, 2002;Pickett et al, 2008). In previous experiments, we showed that PIP3 signalling is necessary for the directionality of the movement response of mesoderm cells during gastrulation in the chick embryo (Leslie et al, 2007).…”
Section: Research Articlementioning
confidence: 79%
“…PDGFRα signals through PI3 kinase to AKT activation Experiments in mice have suggested that one of the major signalling pathways downstream of PDGFRα is activation of PI3 kinase (Klinghoffer et al, 2002;Pickett et al, 2008). In previous experiments, we showed that PIP3 signalling is necessary for the directionality of the movement response of mesoderm cells during gastrulation in the chick embryo (Leslie et al, 2007).…”
Section: Research Articlementioning
confidence: 79%
“…Conversely, an additional study examining the role of PDGFRa signaling in somite-derived structures revealed a cell migration defect in the somite-derived dorsal mesenchyme but no apoptotic or proliferation abnormalities in Pdgfra PI3K/PI3K neural arches or sclerotome (Pickett et al 2008), pointing to regional differences in the response of embryonic tissues to PI3K-mediated PDGFRa signaling.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, paxillin or FAK ablation in mice is embryonic lethal (Sieg et al, 2000;Hagel et al, 2002), and recent studies in vivo have shown that deletion of the PDGF receptor in mice or paxillin in Xenopus laevis resulted in impaired cell polarity and directional cell migration (Iioka et al, 2007;Pickett et al, 2008), giving rise to the developmental defect spina bifida and abnormal convergent extension, respectively (Iioka et al, 2007;Prasad and Montell, 2007;Llense and Martin-Blanco, 2008;Pickett et al, 2008). Furthermore, Rho family GTPase signaling, as well as PAK activity, was significantly disrupted in the absence of the PDGF receptor (Pickett et al, 2008).…”
Section: Discussionmentioning
confidence: 99%